2020
DOI: 10.3390/v12111325
|View full text |Cite
|
Sign up to set email alerts
|

Target-Centered Drug Repurposing Predictions of Human Angiotensin-Converting Enzyme 2 (ACE2) and Transmembrane Protease Serine Subtype 2 (TMPRSS2) Interacting Approved Drugs for Coronavirus Disease 2019 (COVID-19) Treatment through a Drug-Target Interaction Deep Learning Model

Abstract: Previously, our group predicted commercially available Food and Drug Administration (FDA) approved drugs that can inhibit each step of the replication of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) using a deep learning-based drug-target interaction model called Molecule Transformer-Drug Target Interaction (MT-DTI). Unfortunately, additional clinically significant treatment options since the approval of remdesivir are scarce. To overcome the current coronavirus disease 2019 (COVID-19) more eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Similar to velpatasvir, paritaprevir is an antiviral agent against the HCV protease complex that gained a considerable amount of attention in the studies of COVID-19. Through tools like artificial intelligence (AI) deep learning, molecular docking, and, in some studies, molecular dynamics simulation, these investigations unanimously suggested the potential of paritaprevir in inhibiting viral RdRp, S protein, and proteases ( Manikyam and Joshi, 2020 , Shah et al, 2020 , Alamri et al, 2020 , Khan et al, 2020 , Choi et al, 2020 ). Our results expand the current paradigm and suggest that paritaprevir may also be used to target the NBD of csBiP, thereby sabotaging viral activities.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to velpatasvir, paritaprevir is an antiviral agent against the HCV protease complex that gained a considerable amount of attention in the studies of COVID-19. Through tools like artificial intelligence (AI) deep learning, molecular docking, and, in some studies, molecular dynamics simulation, these investigations unanimously suggested the potential of paritaprevir in inhibiting viral RdRp, S protein, and proteases ( Manikyam and Joshi, 2020 , Shah et al, 2020 , Alamri et al, 2020 , Khan et al, 2020 , Choi et al, 2020 ). Our results expand the current paradigm and suggest that paritaprevir may also be used to target the NBD of csBiP, thereby sabotaging viral activities.…”
Section: Resultsmentioning
confidence: 99%
“…proteins are some of the major targets of the coronaviruses, their excessive suppression by targeted therapies may result into the appearance of unprecedented collateral adverse effects such as the male infertility, frequent respiratory infections, and hypertension (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…ACE2, on the other hand, is commonly known to physiologically catalyze the hydrolysis of angiotensin II to angiotensin and contribute to vasodilatation [ 28 , 29 ], and to pathologically facilitate SARS-CoV-2 and similar infections [ 46 ]. Thus, while the TMPRSS2 and ACE2 proteins are some of the major targets of the coronaviruses, their excessive suppression by targeted therapies may result into the appearance of unprecedented collateral adverse effects such as the male infertility, frequent respiratory infections, and hypertension [ 47 , 48 ]. Another crucial target to fight against SARS-CoV-2 is M pro , which cleaves the polyprotein into functional proteins to help in its replication process [ 49 ].…”
Section: Discussionmentioning
confidence: 99%